Sistem Pakar Mendiagnosa Penyakit Polio Menerapkan Metode Hybrid Case Based - Chintami Febri Idris (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
Expert system of a computer system designed to be able to do reasoning like an expert or expert in a particular field. It should be noted, however, that this expert system is not a substitute for an expert or physician but is only for limited equipment, since this expert system is consultative and also has no such properties as a physician who is able to identify in detail the illness experienced by the patient with his or her thoughts . This expert system is made using Hybrid Case Based method. This method is a combination of the system that is Rule Based Reasoning (RBR) and Case Based Reasoning (CBR), this method has a better accuracy than the method running alone. This method will process a symptom so that can be detected disease suffered by the patient.